Determinants of Premarital Sexual Behavior Among the Late Adolescents in Pahang, Malaysia - Minhat, Halimatus Sakdiah; Raja Ismail, Raja Nurul Najwa; Lim, Poh Ying (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Premarital sexual behaviour remains an important sexual and reproductive health issue among adolescents in Malaysia. It is also a prohibited act and considered sinful among the Muslims community. This study aimed to identify the determinants of premarital sexual behaviour among the late adolescents age group in Pahang, Malaysia. Methods: An observational study was conducted among eligible late adolescents, which were recruited using probability sampling method. Only those aged 18 to19 years old, and previously attended the public secondary schools in Malaysia were included, with non-Malaysian, married and those who were absent during the data collection day were excluded. Data was collected using a valid and reliable set of questionnaires measuring the personal (demographic profile, knowledge and attitude), behavioural (premarital sexual behaviour and high-risk activities) and environmental (subjective norms and perceived parental communication) factors. Multiple logistic regression analysis was conducted to identify the determinants of premarital sexual behaviour. Results: A total of 390 adolescents aged 18 and 19 years old participated in this study, with 82.3% of respondents reported never had premarital sexual behaviour. Multiple logistic regression showed that the male and engagement in high-risk activities had higher odds in premarital sexual behaviour respectively (AOR =11.649, 95% CI: 3.615,37.536, p <0.001; AOR=19.224, 95% CI: 7.820,47.262, p <0.001). Conclusion: Male gender and engagement in high-risk activities remained important risk factors towards the ongoing concern related to premarital sexual behaviour among adolescents in Malaysia. Failure to address this issue should be explored and improve accordingly.